Integrative taxonomy revealing a troglobitic new genus of Diplommatinidae from Jiangxi, China (Gastropoda: Caenogastropoda: Cyclophoroidea) - Chen, Zhe-Yu; Lyu, Zhi-Tong; Chen, Hui-Ming (Zootaxa, 2023)
A new subterranean diplommatinid snail is described and illustrated from Jiangxi, China. The species is diagnosed by its cylindrical-fusiform shell and absence of internal columellar lamellae and parietal folds. The morphological and molecular phylogenetic characterization of the new species supports the erection of a new genus, Sohtsuia Z.-Y. Chen, gen. nov. A molecular phylogeny of representative East Asian continental species of Diplommatina Benson, 1949 is provided and the relationships of the new genus are discussed. Sohtsuia diting sp. nov. is described as new species.